General Regulations on the Right to Paid and Unpaid Leave in the Croatian Labour Law - Zlatović, Dragan; Kardum Goleš, Ivana (LeXonomica, 2019)
In this article, authors are referring to the legal framework of the regulation of the right to have leave in new Croatian labour law. The Croatian Labour Act provides for the right to paid leave and the institute of unpaid leave. Unpaid leave is the time when a worker is exempt from labour obligations and for whom the rights and obligations arising from or in connection with the employment relationship are to rest during that time, unless otherwise specified. A paid leave is the time at which a worker is exempt from labour obligations during which he/she is entitled to remuneration, as well as all other employment rights, which is considered to be time consumed at work. The issue of leave, in particular the right to paid leave, is regulated by the Labour Act and the provisions of collective agreements, labour regulations and employment contracts.